One new species in the cockroach genus Jacobsonina Hebard 1929 (Blattodea, Ectobiidae, Blattellinae) from Mainland China - Wu, Keliang; Yue, Qiaoyun; Qiu, Deyi; Liu, Dexing (Zootaxa, 2014)
One new species of Jacobsonina Hebard from China is described and illustrated: Jacobsonina erebis sp. nov.. A key to all known species in this genus, except for J. lugubris (Brunner von Wattenwyl, 1893), based on males, is provided.